2013
DOI: 10.1177/0310057x1304100106
|View full text |Cite
|
Sign up to set email alerts
|

The Clinical Role of Glutamine Supplementation in Patients with Multiple Trauma: A Narrative Review

Abstract: Glutamine is considered an essential amino acid during stress and critical illness. Parenteral glutamine supplementation in critically ill patients has been shown to improve survival rate and minimise infectious complications, costs and hospital length-of-stay. However, glutamine supplementation in patients receiving enteral nutrition and the best method of administration are still controversial. The purpose of this article is to provide a narrative review of the current evidence and trials of enteral and pare… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 88 publications
(110 reference statements)
0
7
0
Order By: Relevance
“…by measuring base deficit, strong anion gap and plasma lactate levels 2224 ). At the same time, metabolic approaches are key in defining effective resuscitation strategies to meet the increased physiologic demands of critically injured patients by providing specific metabolic substrates such as glutamine 12,2527 and arginine 2832 , either alone or in combination with omega-3 fatty acids and nucleotides 33 . Recently, we applied metabolomics technologies to delineate the metabolic derangements in hemorrhaged rodents and critically ill patients to identify shared perturbations of the post-shock metabolic pathways observed in the animal model and the clinical setting 4,6,10,13 .…”
Section: Discussionmentioning
confidence: 99%
“…by measuring base deficit, strong anion gap and plasma lactate levels 2224 ). At the same time, metabolic approaches are key in defining effective resuscitation strategies to meet the increased physiologic demands of critically injured patients by providing specific metabolic substrates such as glutamine 12,2527 and arginine 2832 , either alone or in combination with omega-3 fatty acids and nucleotides 33 . Recently, we applied metabolomics technologies to delineate the metabolic derangements in hemorrhaged rodents and critically ill patients to identify shared perturbations of the post-shock metabolic pathways observed in the animal model and the clinical setting 4,6,10,13 .…”
Section: Discussionmentioning
confidence: 99%
“…Gastrointestinal cancer patients often accompanied by malnutrition and immune dysfunction, thereby slowing the recovery after surgical trauma and increasing mortality. [ 28 29 ] During surgical stress, the consumption of Gln exceeds the synthesis, resulting in depletion of Gln stores. [ 30 ] Moreover, the limited intestinal reserves and surgical fasting period would further aggravating relative lack of Gln.…”
Section: Discussionmentioning
confidence: 99%
“…Major advantages include maintenance of the gastrointestinal function and stress ulcer prevention. Moreover, enteral nutrition helps to improve the gastrointestinal function and thus to support regional defence mechanisms and ultimately to strengthen the immune system [ 3 ], [ 4 ], [ 7 ], [ 27 ], [ 30 ], [ 43 ]. For example, burn patients and patients after surgery for malignant neoplasms who received enteral nutrition therapy had lower complication rates and shorter hospital stays [ 33 ], [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…Clinical observations suggest that the positive effect of early nutritional therapy can be enhanced by adding certain nutrients that have a positive effect on the immune system. Pilot studies have shown that glutamine, arginine and omega-3 fatty acids have positive effects on the immune status of critically ill patients [ 3 ], [ 4 ], [ 5 ], [ 6 ], [ 7 ], [ 8 ], [ 9 ], [ 10 ], [ 11 ], [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation